Δημιουργία θεματικών χαρτών αξιών ακινήτων στο Δήμο Λεμεσού - Τουμάζου, Ανδρέας (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The present thesis titled as ‘’Creation of value thematic maps for the Municipality of Limassol’’ was conducted within the program of undergraduate studies of the Department of Civil Engineering and Geomatics of the Cyprus University of Technology. Aim of this thesis is to investigate and present all factors that influence the market values of real estate and highlight the capabilities of Geometric Information System (GIS) to provide data management, analysis, mapping and final decision-making tool in cases of Real Estate applications. This thesis focuses on two main factors influencing real estate values, location and economic crisis. In 2008 the global economy was hit by a huge financial crisis, which affected our own country as well as the Real Estate Market. In order to research and analyze how these factors affect the Real Estate Market, GIS was used to produce real estate value maps. All the factors that affect the local Real Estate Market were examined for the municipality of Limassol. For the creation of thematic maps, data of sales during the period 2006 to 2014 were used in a GIS model.
Keywords: Real estate; Parcels; Sales; Geographic information system; Thematic maps; Αγορά ακινήτων; Τεμάχια; Αγοραπωλησίες; Γεωγραφικό σύστημα πληροφοριών; Θεματικοί χάρτες